Two millennia of Christianity in Iraq - Brock, Sebastian P. (Islam and Christian-Muslim relations, 2010)
Christianity in Iraq goes back to the very early centuries of Christianity; by the second quarter of the fourth century, the date of the earliest surviving major Syriac author writing in this area, it was clearly already a widespread and firmly established presence. Throughout the ensuing centuries and right up to the present time, it has continually played an important part in the wider society of the region. The present article focuses on certain select aspects of especial significance, in particular, the role of Christian scholars in the course of the ‘translation movement’ under the early ‘Abbasids.